The Effect of Biofertilizer (Jakaba) Fertilizer on Vegetative Growth of Chili Plants (Capsicum annuum L.) - Theresia Viviani Putri Ndese; Decky David Wewurid Kamagi; Helen Joan Lawalata; Yermia Samuel Mokosuli; Marthy Lingkan Stela Tauluh (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Abstract. Chili (Capsicum annuum L.) is a vegetable commodity with considerable economic value. Agricultural soil that hardens, has a high clay content, does not respond to fertilization, reacts sourly, and is poor in nutrient elements and organic matter, causing many agricultural lands to be less productive and even no longer productive. This research aims to determine whether there is an effect of providing Jakaba biofertilizer on the growth of chili plants. This research used a Completely Randomized Design (CRD) with a factorial pattern consisting of 2 factors and 5 replications. The first factor is the fertilizer dose (D), which includes D0 (without fertilizer), D5 (fertilizer dose 5 ml/plant), D10 (fertilizer dose 10 ml/plant), D15 (fertilizer dose 15 ml/plant), D20 (fertilizer dose 20 ml/plant), and D25 (fertilizer dose 25 ml/plant)-planting media (M), which consists of M1 (soil) and M2 (soil: Jakaba = 1: 1), is the second component. Plant height is measured in centimeters, while the number of leaves is calculated in strands. The results of the research obtained show that there was an influence that can be seen from the combination of doses of biofertilizer and planting media on the vegetative growth of chili plants, namely the observation of plant height in the 4th week of M2D25 treatment has a value The highest is 10.18 ± 0.19 compared to other treatments, so that based on the Kolmogorov test and followed by the Anova test, it has a significant degree of 0.05, which means Ho is accepted and Ha is rejected. Then, when observing the number of leaves, we looked at the 4th week where the M2D20 treatment had the highest average number of leaves, namely 8.6 ± 0.55 compared to other treatments. So, based on the Kolmogorov test followed by the Anova test, it has a significant degree of 0.05, saying that Ho is accepted and Ha is rejected.